Epidemiological characterization of human anthrax cases in Peru, 2015 - 2019 - Córdova-Díaz, Ever F. (2022)
Introduction. The epidemiology of anthrax in Peru is poorly understood. Its high epidemic and epizootic potential could threaten public health, especially in its endemic regions. Objective. To characterize cases of human anthrax in Peru from 2015 to 2019. Methods. A retrospective cross-sectional study was carried out; based on data from the National Epidemiological Surveillance System and investigations of anthrax outbreaks from 2015 to 2019 in Peru. Results. 71 cases of human anthrax were registered, 34 % (n = 24) confirmed and 66 % (n = 47) probable. The most affected were males (55 %) and the age group from 30 to 59 years (45 %) , distributed mainly on the north coast of the country. The self-limited cutaneous form was the most frequent clinical presentation. 94% (n = 67) of the cases had contact with infected cattle. Conclusions. The cases of human anthrax in Peru appear as focalized outbreaks in areas with a history of zoonotic transmission. This report aims to contribute to the epidemiological knowledge of this disease and serve as input in the implementation of prevention and control measures.